Prostorska informacija v stavčno zasnovani slovarski definiciji - Gantar, Polona (Slavistična revija, 2014)
The paper describes the design of semantic frames, i.e., syntactic realizations of individual verbal meanings in the Slovene Lexical Database, which represent the basis for formulation of sentence-level lexical definitions and allow the use with language technologies. Verbal meanings containing a spatial component in their semantic frames are analyzed from the point of view of the syntactic patterns in which they are typically manifested and from the point of view of lexical realization of individual arguments as evident from collocations.
Keywords: kolokacije; leksikologija; lexicology; semantics; semantika; Slovene; slovenščina; stavčni vzorci